2016
DOI: 10.1007/jhep01(2016)154
|View full text |Cite
|
Sign up to set email alerts
|

T-duality without isometry via extended gauge symmetries of 2D sigma models

Abstract: Target space duality is one of the most profound properties of string theory. However it customarily requires that the background fields satisfy certain invariance conditions in order to perform it consistently; for instance the vector fields along the directions that T-duality is performed have to generate isometries. In the present paper we examine in detail the possibility to perform T-duality along non-isometric directions. In particular, based on a recent work of Kotov and Strobl, we study gauged 2D sigma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 52 publications
0
34
0
Order By: Relevance
“…We do not give the complete account of all possible cases (the interested reader can find it in [1,2,5,8]), because our concern is different. We will show that the Lie algebroid generalisation of the intermediate gauge theory proposed by CDJ in [3] can be rewritten, using appropriate field redefinitions, in the standard non-Abelian T-duality form (2.4). It follows that the CDJ proposal cannot describe more general T-duality patterns than that of traditional non-Abelian T-duality.…”
Section: Preliminaries On the Non-abelian T-dualitymentioning
confidence: 99%
See 2 more Smart Citations
“…We do not give the complete account of all possible cases (the interested reader can find it in [1,2,5,8]), because our concern is different. We will show that the Lie algebroid generalisation of the intermediate gauge theory proposed by CDJ in [3] can be rewritten, using appropriate field redefinitions, in the standard non-Abelian T-duality form (2.4). It follows that the CDJ proposal cannot describe more general T-duality patterns than that of traditional non-Abelian T-duality.…”
Section: Preliminaries On the Non-abelian T-dualitymentioning
confidence: 99%
“…In Section 6, we illustrate a few examples where, by simple field redefinitions, the traditional isometric Roček-Verlinde gauge theory may look like a non-trivial Lie algebroid gauge theory. In particular, we unmask the "non-isometric T-duality" example of CDJ presented in [3]. Finally, we end with a short discussion.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Recently, a two-dimensional gauged sigma model with a two-form b-field with three dimensional Wess-Zumino term [14] is analyzed related to T-duality in string theory [4,5,7,8,9,10]. For such an application, it is interesting to generalize a momentum section in a pre-multisymplectic manifold.…”
Section: Introductionmentioning
confidence: 99%
“…However, there are subtleties to consider when attempting to apply this to the study of non-linear sigma models. When this procedure was applied to the study of T-duality there was an initial belief that it let to a notion of 'non-isometric T-duality' [4,6]. It was later shown that gauge invariance of the action actually rendered the non-isometric T-duality proposal equivalent to non-abelian T-duality [2].…”
mentioning
confidence: 99%